Program aktualności krajowych i zagranicznych Nr 7. (Gdynia : [s.n.], 1948)
Afisz inf. o seansach w listopadzie 1946 r.
Keywords: Kino polskie -- 1945-1960 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne